AVALIAR POR COMPETÊNCIAS: UMA DISCUSSÃO A PARTIR DO ENSINO PROFISSIONALIZANTE - Zambieri, Solange Cristina (2014)
The objective of this investigation is to search for a better understanding of the complex and varied universe of evaluation of competences in the technical teaching , having in mind the competences described in the Lei de Diretrizes e Bases da Educação Nacional in effective (law no.9394/96) and the new official documents, and also the theory behind this discussion, under the educational and market principles, since the nineties, as well as the technical documents that guide the schools which offer technical courses. In order to understand the present and the future, the rescue of the evolution of this kind of teaching has become important, from the time in which classes used to be given with the only goal of applying some economy needs at the lyceums, in the eighteenth and nineteenth centuries, and the definite impulse given from the First Republic (President Nilo Peçanha) onward. Even so, it has been found from the theoretical framework used, that some aspects continued being the same, even after centuries of history, as the strong discrimination against this same kind of technical teaching, the spoon-feeding connotation and the twofold character of the teaching in Brazil, where the prevailing vision was that the technical teaching was applied for the poor and the regular teaching for the rich. The evaluation of competences has become more important as globalization increased and the consequent deep transformations of the world work market, which demanded a more qualified workforce. However, people should go beyond knowing how to do a job on a daily basis (Kuenzer, 2002). As, for example, learn and know how to transform knowledge, abilities, interests and will power into practical results (Resende, 2000), not only in Brazil, for sure. We also followed the efforts of adjustment to the technical teaching in other countries, such as the USA, France, Great Britain and organizations such as UNESCO and OCDE. This way, the employees are paid for their new aptitudes and performance, and not only for their positions (Arruda, 2000). These issues have become a real big problem, a routine, and with a sense of urgency which deserves its relevance and the present importance. In this sense, this abstract discusses these issues from the point-of-view of those teachers who evaluate the technical teaching and deal every day with this complexity, taking into consideration common sense and the working conditions. As a result, it has been noticed that the evaluation through competences has reached its importance as a system of analysis of results and practices in such a way that teachers can watch their students systematically not only at the end of their studies.